Therapeutic Effect of Rapamycin-Loaded Small Extracellular Vesicles Derived from Mesenchymal Stem Cells on Experimental Autoimmune Uveitis - Li, Huan; Zhang, Zhihui; Li, Yongtao; Su, Lin; Duan, Yanan; Zhang, Hui; An, Jinying; Ni, Tianwen; Li, Xiaorong; Zhang, Xiaomin (Frontiers in Immunology, 2022)
Autoimmune uveitis is a major cause of vision loss and glucocorticoids are major traditional medications, which may induce serious complications. Rapamycin has been demonstrated to exhibit immunosuppressive effects and is promising to be used in treating uveitis by intravitreal injection. However, repeated and frequent intravitreal injections increase the risk of severe ocular complications, while the efficacy of subconjuctival injection of rapamycin is low since it is difficult for rapamycin to penetrate eyeball. Recently, small extracellular vesicles (sEVs) have attracted considerable research interest as natural drug delivery systems that can efficiently cross tissues and biological membranes. sEVs derived from mesenchymal stem cells (MSC-sEVs) also can exert immunosuppressive effect and ameliorate experimental autoimmune uveitis (EAU). The aim of this study was to construct a Rapamycin-loaded MSC-sEVs delivery system (Rapa-sEVs) and investigate its therapeutic effect on EAU by subconjunctival injection. Rapa-sEVs were prepared by sonication and characterized by nanoparticle tracking analysis, transmission electron microscopy, and western blotting. Clinical and histological scores were obtained to assess the treatment efficacy. Additionally, T cell infiltration was evaluated by flow cytometry. The results indicated that Rapa-sEVs could reach the retinal foci after subconjunctival injection. Compared to sEVs and rapamycin alone, Rapa-sEVs can produce a more marked therapeutic effect and reduce ocular inflammatory cell infiltration. Overall, MSC-sEVs have significant potential for the delivery of rapamycin to treat EAU. Subconjunctival injection of Rapa-sEVs may be contender for efficacious steroid-sparing immunomodulatory therapy.